1999
DOI: 10.1007/s11627-999-0043-8
|View full text |Cite
|
Sign up to set email alerts
|

Histological study of in vitro development of adventitious buds on leaf explants of oriental beech (Fagus orientalis lipsky)

Abstract: Adventitious shoots were induced on the proximal portion of leaves excised from Fagus orientalis shoot cultures derived from a 2-mo.-old or a 4-yr-old seedling. Up to 90% of the explants formed between 13 and 19 buds after culture on Woody Plant Medium containing 2.9 pM indole-3-acetic acid and 4.5 pM thidiazuron. Adventitious buds developed mostly on petiole stub callus, but also on the midvein. The histological events leading to shoot organogenesis were examined. Some shoots developed directly from subepider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
(20 reference statements)
2
3
0
1
Order By: Relevance
“…TDZ concentrations and the presence of IAA greatly influence the frequency, growth and the number of formed calluses, buds and shoots, with 10µM TDZ and 5µM IAA being the most suitable range ( Table 1). The above findings are consistent with the results noted by other authors (Cuenca and Vieitez 1999;Meiners et al 2007). Several factors are known to influence callus production and shoot organogenesis, in particular explant type, medium type, the presence of plant growth regulators (especially auxins) and the genotype (Brown and Thorpe 1986).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…TDZ concentrations and the presence of IAA greatly influence the frequency, growth and the number of formed calluses, buds and shoots, with 10µM TDZ and 5µM IAA being the most suitable range ( Table 1). The above findings are consistent with the results noted by other authors (Cuenca and Vieitez 1999;Meiners et al 2007). Several factors are known to influence callus production and shoot organogenesis, in particular explant type, medium type, the presence of plant growth regulators (especially auxins) and the genotype (Brown and Thorpe 1986).…”
Section: Discussionsupporting
confidence: 93%
“…The dose of TDZ is critical in shoot organogenesis (Lu 1993). Although TDZ supports regeneration in selected Vaccinium (Cao and Hammerschlang 2000) and Rhododendron (Tomsone and Gertnere 2003;Tomsone et al 2004) species as well as in Leucopogon verticillatus (Anthony et al 2004), its effectiveness in regener- According to several studies, auxins are required for the regeneration of adventitious shoots because TDZ and auxin combinations applied in the medium increase the number of responsive explants (Cuenca and Vieitez 1999;Singh et al 2003;Meiners et al 2007). This study demonstrated that TDZ induced explant swelling, callus formation and, in several cases, shoot differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The "target" cell is considered the "competent" cell for shoot induction, and the formation of target cells may be interpreted in terms of competence acquisition. Similar observations of such changes in the cell division model during the differentiation of promeristemoids have been reported for other species, such as Fagus orientalis (Cuenca & vieitez, 1999) and Jatropa curcas (varshney, Sangapillai, Patil, & Johnson, 2011).…”
Section: Discussionsupporting
confidence: 86%
“…during the formation of adventitious buds in foliar explants of beech have been described in detail by Cuenca & vieitez (1999). Hu, Liu, Yan & Xie (2005) also observed differentiation of a long narrow meristematic zone in the subepidermis of petioles of Amorphophallus, from which the meristemoids were formed.…”
Section: Discussionmentioning
confidence: 89%
“…Direct shoot organogenesis from parenchymatic cells has been observed in Lycopersicon esculentum (Pugliesi et al 1999), Fagus orientalis (Cuenca and Vieitez 1999) and Achras sapota (Purohit et al 2004). The pattern of shoot development, via the formation of meristematic domes, was similar to those of Alstroemeria (Lin et al 1998), F. orientalis (Cuenca and Vieitez 1999), Jatropha integerrima (Sujatha et al 2000), L. esculentum (Pugliesi et al 1999), and A. sapota (Purohit et al 2004). In the last two species, as well as in chestnut (Castanea sativa Mill.…”
Section: Discussionmentioning
confidence: 99%